2024
DOI: 10.1002/adom.202302641
|View full text |Cite
|
Sign up to set email alerts
|

Antimony Doped Hybrid Zinc Halide Crystals with Tunable Light Emission and Long‐Term Stability

Yaqing Zhang,
Yan Jiang,
Qi Zhang
et al.

Abstract: As a class of emerging photoluminescent materials, hybrid halide crystals have drawn research attention for their potential application in the fields of light‐emitting, security, and waveguide. Nevertheless, hybrid halide crystals containing antimony with long‐term stability and tunable light emission are still increasingly in demand. In this work, serial new hybrid halide crystals (BZA)2ZnCl4·2H2O:xSb3+ (x = 0–0.2, x represents the reaction ratio) and (BZA)2SbCl5 are synthesized (BZA = 2,4‐diamino‐6‐phenyl‐1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…0D OIMHs with optically active ions such as Mn 2+ and Sb 3+ as a metal center always feature typical optical emission due to the intrinsic electronic transition of these metal ions. 12–15 For instance, the (MTP) 2 MnBr 4 (MTP: methyltriphenylphosphonium) 12 and (BZA) 2 SbCl 5 (BZA = 2,4-diamino-6-phenyl-1,3,5-triazine) 13 crystals which possess a 0D structure display strong blue and orange emissions under the excitation of ultra violet (UV) light. However, in OD OIMHs with Zn 2+ or Cd 2+ as metal centers, the optical emission mostly originates from the electronic transition of the organic component or the self-trapped excitons (STEs).…”
Section: Introductionmentioning
confidence: 99%
“…0D OIMHs with optically active ions such as Mn 2+ and Sb 3+ as a metal center always feature typical optical emission due to the intrinsic electronic transition of these metal ions. 12–15 For instance, the (MTP) 2 MnBr 4 (MTP: methyltriphenylphosphonium) 12 and (BZA) 2 SbCl 5 (BZA = 2,4-diamino-6-phenyl-1,3,5-triazine) 13 crystals which possess a 0D structure display strong blue and orange emissions under the excitation of ultra violet (UV) light. However, in OD OIMHs with Zn 2+ or Cd 2+ as metal centers, the optical emission mostly originates from the electronic transition of the organic component or the self-trapped excitons (STEs).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, lead-free perovskites, such as double perovskites and low-dimensional perovskites, have attracted great interest in realizing excitation-dependent emission due to several intrinsic advantages including high photoluminescence quantum yields (PLQYs), low-toxicity, and low-cost solution processing. These systems possess unique soft lattices and strong quantum confinement, which endow them with broadband self-trapped exciton (STE) emission. The existence of multiple emission centers, including STEs, ligands, and doping ions, renders them a perfect platform to achieve excitation-dependent emission. For example, Kuang et al reported a zero-dimensional (0D) indium–antimony alloyed halide perovskite, BAPPIn 1.996 Sb 0.004 Cl 10 , which emits bright yellow light and white light with PLQYs of ca. 100 and 44% at 320 and 365 nm excitation, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, low-dimensional organic-inorganic metal halide (OIMH) family can be considered a new highly promising candidate for RTP material with synergistic merits of both inorganic and organic components. [14][15][16][17] Specifically, the inherent RTP properties of organic substrates significantly contribute to the diversification of luminescent properties of hybrid halides. Meanwhile, the soft crystal lattice results in large deformation of metal halide units under the photoexcitation due to a strong electron-phonon coupling effect, which is in favor of the formation of triplet excited states as well as associated phosphorescence.…”
Section: Introductionmentioning
confidence: 99%